Integration of gender considerations in climate-smart agriculture R4D in South Asia: Useful research questions - Farnworth, Cathy Rozel; Badstue, Lone B.; Jat, Mangi Lal; Rai, M.; Agarwal, T. (International Maize and Wheat Improvement Center, 2018)
Aimed at researchers working with climate-smart agriculture in South Asia, this resource suggests a set of issues to consider in relation to the integration of gender in climate-smart agricultural research for development. Climate change often exacerbates the problems and inequities that poor rural women face. The feminization of agriculture underscores the need to ensure that both men and women are able to learn about, try out, take up, and benefit from improved agricultural technologies, including climate-smart practices.